Potential Effects of the Loss of Native Grasses on Grassland Invertebrate Diversity in Southeastern Australia. (1st December 2014) - Clay, Roger Edgcumbe
Abstract : Reduction in area of the southeastern temperate grasslands of Australia since European settlement has been accompanied by degradation of remaining remnants by various factors, including the replacement of native plant species by introduced ones. There are suggestions that these replacements have had deleterious effects on the invertebrate grassland community, but there is little evidence to support these suggestions. In the eastern Adelaide Hills of South Australia, four grassland invertebrate sampling areas, in close proximity, were chosen to be as similar as possible except for the visible amount of native grass they contained. Sample areas were surveyed in four periods (summer, winter, spring, and a repeat summer) using pitfall traps and sweep-netting. A vegetation cover survey was conducted in spring. Morphospecies richness and Fisher's alpha were compared and showed significant differences between sample areas, mainly in the summer periods. Regression analyses between morphospecies richness and various features of the groundcover/surface showed a strong positive and logical association between native grass cover and morphospecies richness. Two other associations with richness were less strong and lacked a logical explanation. If the suggested direct effect of native grass cover on invertebrate diversity is true, it has serious implications for the conservation of invertebrate biodiversity.